LITERATURE ANALYSIS ON PLANT DEVELOPMENTAL COORDINATION AND ITS REGULATION MECHANISMS - nursaldila, nursaldila (Universitas Lancang Kuning, 2025)
Plant development involves the results of complex interactions between genetic regulation, hormones, and environmental responses. This article aims to provide an analysis of plant development coordination and its regulatory mechanisms, to reveal how plants coordinate their growth and adapt to dynamic environments. The method used is a descriptive qualitative approach using a systematic literature review method to identify, classify, and analyze. Article searches were carried out through various scientific databases such as Google Scholar, ScienceDirect and pubmed. Plant development coordination involves complex growth and differentiation processes. Starting with germination triggered by water and enzyme activity, followed by primary growth through apical meristems that produce plant organs (roots, stems, leaves, flowers, fruits, and seeds) and secondary growth, which involves lateral meristems that cause thickening of stems and roots. In addition, genetic regulation functions as a mechanism that allows plants to grow, develop, and respond to the environment effectively. Hormones such as auxins, gibberellins, cytokinins, ethylene, and abscisic acid work together to regulate growth and stress responses. Plants can also remember previous stress through epigenetic modifications to increase their resilience to repeated stress. All of these systems allow plants to adapt and survive in changing environmental conditions.